Pseudoscleroderma associated with POEMS syndrome - Wysocka-Dubielecka, Kalina; Bizoń, Andrzej; Głogowska, Katarzyna; Mączyńska-Karcz, Dorota; Łoza, Katarzyna; Kalbarczyk, Kazimierz; Janeczek, Oskar; Braszkiewicz, Marek (Dermatology Review/Przegląd Dermatologiczny, 2019)
POEMS syndrome is a rare paraneoplastic disorder associated with plasma cell dyscrasia. The acronym stands for coexisting polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin changes. Other relevant features of the syndrome are papilledema, sclerotic bone lesions, Castleman’s disease, thrombocytosis, weight loss and increased vascular endothelial growth factor levels. The diagnostic criteria for POEMS are as follows: major criteria: polyneuropathy, monoclonal plasma cell dyscrasia; minor criteria: sclerotic bone lesions, Castleman’s disease, organomegaly, endocrinopathies, edemas, skin changes, papilledema. To make a diagnosis, 2 major criteria and 1 minor criterion are required. We present a patient with pseudoscleroderma, polyneuropathy, hypothyroidism, monoclonal gammopathy, edemas and weight loss, who was diagnosed with POEMS syndrome as a result of interdisciplinary cooperation.